Protective effect of prior physical conditioning on relaxing response of corpus cavernosum from rats made hypertensive by nitric oxide inhibition - Claudino, M. A.; Priviero, F. B. M.; Camargo, E. A.; Teixeira, C. E.; De Nucci, G.; Antunes, E.; Zanesco, A. (Nature Publishing Group, 2007)
The aim of this work was to evaluate the influence of run training on the responsiveness of corpus cavernosum (CC) from rats made hypertensive by treatment with nitric oxide (NO) synthesis inhibitor. Wistar rats were divided into sedentary control (C-SD), exercise training (C-TR), N(omega)-nitro-L-arginine methyl ester (L-NAME) sedentary (LN-SD) and L-NAME trained (LN-TR) groups. The run training program consisted in 8 weeks in a treadmill, 5 days/week, each session lasted 60 min. L-NAME treatment (2 and 10mg/rat/day) started after 4 weeks of prior physical conditioning and lasted 4 weeks. Concentration-response curves were obtained for acetylcholine (ACh), sodium nitroprusside (SNP), sildenafil and BAY 41-2272. The effect of electrical field stimulation (EFS) on the relaxations responses of CC was evaluated. Run training prevented the arterial hypertension induced by L-NAME treatment (LN-SD: 135+/-2 and 141+/-2 mm Hg for both doses of L-NAME) compared to LN-SD groups (154+/-1 and 175+/-2 mm Hg, for 2 and 10 mg of L-NAME, respectively). Run training produced an increase in the maximal responses (E(max)) of CC for ACh (C-SD: 47+/-3; C-TR: 5271; and LN-TR: 53+/-3%) and SNP (C-SD: 8971; C-TR: 9871; and LN-TR: 95+/-1%). Both potency and E(max) for ACh were reduced in a dose of 10 mg of L-NAME, and run training restored the reduction of E(max) for ACh. No changes were found for BAY 41-2271 and sildenafil. Relaxing responses to EFS was reduced by L-NAME treatment that was restored by prior physical conditioning. In conclusion, our study shows a beneficial effect of prior physical conditioning on the impaired CC relaxing responses in rats made hypertensive by chronic NO blockade.
Keywords: corpus cavernosum; nitric oxide; arterial hypertension; relaxing response; physical exercise